The heterogeneity of attenuated and brief limited psychotic symptoms: association of contents with age, sex, country, religion, comorbidities, and functioning - Theisen, Christian; Rosen, Marlene; Meisenzahl, Eva; Koutsouleris, Nikolaos; Lichtenstein, Theresa; Ruhrmann, Stephan; Kambeitz, Joseph; Kambeitz-Ilankovic, Lana; Riecher-Rössler, Anita; Chisholm, Katharine; Upthegrove, Rachel; Antonucci, Linda A.; et al. (Frontiers in Psychiatry, 2023)
The Attenuated Psychosis Symptoms (APS) syndrome mostly represents the ultra-high risk state of psychosis but, as does the Brief Intermittent Psychotic Symptoms (BIPS) syndrome, shows large variance in conversion rates. This may be due to the heterogeneity of APS/BIPS that may be related to effects of culture, sex, age, and other psychiatric morbidities. Thus, we investigated the different thematic contents of APS and their association with sex, age, country, religion, comorbidity and functioning to gain a better understanding of the psychosis-risk syndrome.Method: A sample of 232 clinical high-risk subjects according to ultra-high risk and basic symptom criteria was recruited as part of a European study conducted in Germany, Italy, Switzerland and Finland. Case vignettes, originally used for supervision of inclusion criteria, were investigated for APS/BIPS contents, which were compared for sex, age, country, religion, functioning and comorbidities using chi-squared tests and regression analyses.We extracted 109 different contents, mainly of APS (96.8%): 63 delusional, 29 hallucinatory, and 17 speech-disorganized contents. Only 20 contents (18.3%) were present in at least 5% of the sample, with paranoid and referential ideas being most frequent. Thirty-one (28.5%) contents, in particular bizarre ideas and perceptual abnormalities, demonstrated an association with age, country, comorbidity or functioning, with regression models of country and obsessive-compulsive disorders explaining most of the variance: 55.8% and 38.3%, respectively. Contents did not differ between religious groups.Psychosis-risk patients report a wide range of different contents of APS/BIPS, underlining the psychopathological heterogeneity of this group but also revealing a potential core set of contents. Compared to earlier reports on North-American samples, our maximum prevalence rates of contents were considerably lower; this likely being related to a stricter rating of APS/BIPS and cultural influences, in particular higher schizotypy reported in North-America. The various associations of some APS/BIPS contents with country, age, comorbidities, and functioning might moderate their clinical severity and, consequently, the related risk for psychosis and/or persistent functional disability.